Monthly versus daily administration of vitamin D3 in children: a retrospective propensity score-matched study - Choi, Jinjoo; Choe, Yunsoo; Yang, Seung (Frontiers in Endocrinology, 2023)
Objectives: We aimed to evaluate the efficacy and safety of monthly vitamin D3 administration compared to a daily dosing regimen in healthy children with vitamin D deficiency. Methods: This retrospective study included vitamin D deficient (serum 25-hydroxyvitamin D [25(OH)D] < 20 ng/mL) children with precocious puberty who received gonadotropin-releasing hormone agonist every 4 weeks between December 2019 and November 2022. We used propensity scores to 1:1 match daily (1,000 IU daily) and monthly (25,000 IU per 4 weeks) administration of vitamin D3 based on age, sex, body mass index Z-scores, season of blood collection, and baseline serum 25(OH)D concentrations. Results: Of 299 children, 192 were matched based on propensity scores (126 girls and 66 boys, 10.5 ± 1.4years). After a mean follow-up of 5.9 months (standard deviation [SD] 2.5 months), the monthly group showed a statistically significant increase in serum 25(OH)D concentrations (10.9 ± 5.3 vs. 8.2 ± 7.2 ng/mL; p = 0.018), higher corrected dose-response (12.3 ± 5.9 vs. 8.2 ± 7.2 ng/mL increase per 1,000 IU daily; p = 0.002), and a higher proportion of patients attaining 25(OH)D > 20 ng/mL (78.1% vs. 58.3%,; p=0.005) compared with the daily group. No cases of hypercalcemia were observed in either group. Conclusions: Monthly administration of vitamin D3 may be an effective and safe alternative to correct hypovitaminosis D in pediatric population, possibly attributed to enhanced compliance.